ผลของโปรแกรมการให้ข้อมูลอย่างมีแบบแผนร่วมกับการฟังดนตรีต่อความวิตกกังวลหลังการสวนหลอดเลือดหัวใจของผู้ป่วยโรคกล้ามเนื้อหัวใจขาดเลือดเฉียบพลัน - นิพนธ์ วาตาดา (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
This quasi - experimental pretest - posttest with control group research aimed to study effects of giving planned information combined with music listening program on anxiety after cardiac catheterization among acute myocardial infarction patients. The participants were acute myocardial infarction patients who were received first emergency cardiac catheterization at Maharat Nakhonratchasima hospital, Nakhonratchasima, Thailand. The participants were assigned to the control and experimental groups (22 for each group). The control group was received conventional nursing care, while the experimental group received the giving planned information combined with music listening program. The program was conducted for 2 days after cardiac catheterization at Cardiac Care Unit. Data were collected by using demographic information sheet, The State - Trait Anxiety Inventory form Y-1 (Spielberger, 1983), knowledge questionnaire related to coronary heart disease and one item of musical satisfaction. The content validity index of The State - Trait Anxiety Inventory form Y-1 and knowledge questionnaire related to coronary heart disease were .75 and .93. There reliabilities were .82 and .90, respectively. Dependent and independent t-test statistic were used to analyze the data. The results revealed that : 1. The mean score of anxiety after receiving the giving planned information combined with music listening program was significantly lower than that before receiving the program at the significant level of .05. 2. The mean score of anxiety after receiving the giving planned information combined with music listening program in experimental group was significantly lower than that in the control group at the significant level of .05.